Cross-domain password-based authenticated key exchange revisited - CHEN, Liqun (Institutional Knowledge at Singapore Management University, 2014)
We revisit the problem of secure cross-domain communication between two users belonging to different security domains within an open and distributed environment. Existing approaches presuppose that either the users are in possession of public key certificates issued by a trusted certificate authority (CA), or the associated domain authentication servers share a long-term secret key. In this article, we propose a generic framework for designing four-party password-based authenticated key exchange (4PAKE) protocols. Our framework takes a different approach from previous work. The users are not required to have public key certificates, but they simply reuse their login passwords, which they share with their respective domain authentication servers. On the other hand, the authentication servers, assumed to be part of a standard PKI, act as ephemeral CAs that certify some key materials that the users can subsequently use to exchange and agree on as a session key. Moreover, we adopt a compositional approach. That is, by treating any secure two-party password-based key exchange (2PAKE) protocol and two-party asymmetric-key/symmetric-keybased key exchange (2A/SAKE) protocol as black boxes, we combine them to obtain generic and provably secure 4PAKE protocols.